Corrosion-resistant composite coating and preparation method thereof

The first corrosion-resistant coating composed of Al, Si, Al2O3, etc. is prepared on the energy equipment flow component, and the second corrosion-resistant coating composed of Al, Co, Cr, etc. is prepared by laser cladding on the basis of it. , solves the corrosion resistance problem of existing coating technology in high temperature, long time and low stress environments, and achieves efficient and long-lasting coating performance.

CN119392246APending Publication Date: 2025-02-07HUANENG HUNAN YUEYANG POWER GENERATION CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411586258.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing coating technology is difficult to meet the corrosion resistance needs of energy equipment flow components in high temperature, long time and low stress environments, and the process is complex, the production efficiency is low, the adhesion is poor, and it is easy to fall off.

Method used

Using a corrosion-resistant composite coating, a first corrosion-resistant coating consisting of Al, Si, Al2O3, NH4Br, Cr2O3 and MgO is prepared by laser cladding on the substrate. A second corrosion-resistant coating consisting of Al, Co, Cr, Ni, Fe and Ti.

Benefits of technology

It significantly improves the corrosion resistance and mechanical properties of the coating, extends the service life, simplifies the process flow, and improves production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119392246A_ABST
    Figure CN119392246A_ABST
Patent Text Reader

Abstract

The invention discloses a corrosion-resistant composite coating and a preparation method thereof, and belongs to the technical field of composite coatings. The method comprises the steps that firstly, a base layer is coated with a first corrosion-resistant raw material, a first corrosion-resistant coating is obtained, and the first corrosion-resistant raw material is obtained from a solid-phase component and a liquid-phase component; on the basis of a first corrosion-resistant coating, a second corrosion-resistant coating is prepared through laser cladding, in the process of preparing the second corrosion-resistant coating, a high-entropy alloy is introduced, an aluminum element serves as a core element and can have good metallurgical bonding performance with the first corrosion-resistant coating, and meanwhile, due to the preparation method of laser cladding, the corrosion resistance of the second corrosion-resistant coating is improved at the high temperature. The second corrosion-resistant coating is added into the first corrosion-resistant coating, the bonding performance with the first corrosion-resistant coating is further enhanced, the high-entropy high-temperature alloy serves as the outermost coating, the porosity is low, the components are uniform, Co, Ce, Ni and Ti in the high-entropy high-temperature alloy can improve the corrosion resistance of the coating, the hardness of the whole structure after the second corrosion-resistant coating is added is high, and the service life can be prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite coatings, and in particular relates to a corrosion-resistant composite coating and a preparation method thereof. Background Art

[0002] Corrosion has become a common industry problem and technical pain point that restricts the safe production and operation of the entire energy equipment, causing huge losses. Taking the power industry as an example, pipe blockage and pipe burst accidents caused by scale problems on the inner wall of flow-through components account for more than 50% of boiler non-shutdown accidents, resulting in an increase of more than 20% in the operating cost and material cost of the unit. Existing high-temperature coating technology is mostly used for hot-end components such as aircraft engine blades, rotors, and turbine disks with high temperatures, short action times, and small sizes. Existing coating technology is no longer applicable to the large aspect ratio structural characteristics of energy equipment flow-through components, and the high temperature, long time, and low stress service environment.

[0003] Boiler flue gas often contains sulfides, chlorides and nitrogen oxides, which are more likely to affect large aspect ratio flow parts in high temperature and high steam content environments. The existing multi-layer coating method is usually used to improve the corrosion resistance of the coating. For example, a multi-layer coating system can be formed by applying a layer of primer on the metal surface and then a layer of topcoat. The primer can enhance the adhesion of the topcoat to the metal surface, while the topcoat can provide excellent corrosion resistance. In addition, the high temperature resistance of the coating can be improved by adding some high temperature resistant ceramic particles, such as aluminum oxide, titanium oxide, etc.

[0004] However, existing multi-layer coating systems usually require multiple coatings, with complex processes and low production efficiency. Secondly, existing coating materials are prone to phase change or decomposition in high temperature environments, resulting in coating failure. In addition, existing coating materials often have poor adhesion at high temperatures and are prone to falling off, thus affecting the corrosion resistance of the coating. Summary of the invention

[0005] The purpose of the present invention is to overcome the above-mentioned shortcomings of the prior art and provide a corrosion-resistant composite coating and a preparation method thereof, so as to solve the problem that the coatings of the prior art are difficult to meet the service environment of high temperature and strong corrosion.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A method for preparing a corrosion-resistant composite coating comprises the following steps:

[0008] Step 1: Weigh Al powder, Si powder, Al 2 O 3 Powder and NH 4 Br powder, and solid phase components were obtained after ball milling; Al(H 2 PO4)3 and water glass as solvent, with Cr 2 O 3 and MgO as solutes, mixing and stirring to obtain a liquid phase component; mixing the solid phase component and the liquid phase component to obtain a first corrosion-resistant raw material, coating the first corrosion-resistant raw material on the surface of the substrate, and obtaining a first corrosion-resistant coating after drying, curing and heat treatment;

[0009] Step 2, mix Al powder, Co powder, Cr powder, Ni powder, Fe powder and Ti powder, obtain a second corrosion-resistant powder after ball milling, lay the second corrosion-resistant powder on the first corrosion-resistant coating, and obtain a second corrosion-resistant coating through laser cladding treatment; the molar fraction of Al powder in the second corrosion-resistant powder is 25% to 30%, the molar fraction of Ti powder is 5% to 10%, and the molar fractions of the other four powders are equal.

[0010] A further improvement of the present invention is:

[0011] Preferably, in step 1, the solid phase component is composed of 45-60% Al powder, 20-40% Si powder, and 15-20% Al 2 O 3 powder and 1-5% NH 4 Br powder composition.

[0012] Preferably, in step 1, in the liquid phase component, Cr 2 O 3 The mass fraction of Ni is 10-30%, and the mass fraction of MgO is 1-15%.

[0013] Preferably, in step 1, the mixing ratio of the solid phase component and the liquid phase component is 10 g: (3-7) mL.

[0014] Preferably, in step 1, the solid phase component and the liquid phase component are mixed by ball milling, and the ball milling time is 6-24 hours; the curing temperature is 300-450° C., and the curing time is 24-48 hours; the heat treatment temperature is 980-1150° C., and the heat treatment time is 8-15 minutes.

[0015] Preferably, in step 2, before laying the second corrosion-resistant powder on the first corrosion-resistant coating, the surface of the first corrosion-resistant coating is cleaned with dilute hydrochloric acid.

[0016] Preferably, in step 3, the ball milling speed during the ball milling of Al powder, Co powder, Cr powder, Ni powder, Fe powder and Ti powder is 200-300 r / min, and the ball milling time is 8-20 h.

[0017] Preferably, the second corrosion-resistant powder is dried after ball-milling and mixing, and the drying temperature is 100-120° C. and the drying time is 1-2 hours.

[0018] Preferably, the laser cladding power is 2000-3000W, the scanning speed is 8-12mm / s, the powder feeding speed is 5-10g / min, the spot diameter is 3-5mm, the powder feeding gas and the protective gas are high-purity argon, and the cladding overlap rate is 40-50%.

[0019] A corrosion-resistant composite coating prepared by any one of the above methods, comprising a first corrosion-resistant coating composited on a substrate, and a second corrosion-resistant coating composited on the first corrosion-resistant coating;

[0020] The first corrosion-resistant coating is composed of Al, Si, Al 2 O 3 NH 4 Br, Cr 2 O 3 and MgO, and the second corrosion-resistant coating consists of Al, Co, Cr, Ni, Fe and Ti.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The invention discloses a method for preparing a corrosion-resistant composite coating. The coating firstly coats a first corrosion-resistant raw material on a base layer to obtain a first corrosion-resistant coating. The first corrosion-resistant raw material is obtained by mixing a solid phase component and a liquid phase component. The solid phase component contains an aluminum element with excellent performance as a core element, which can form an Al2O3 layer with excellent corrosion resistance. 2 O 3 Adding silicon to the first layer of corrosion-resistant coating can generate SiO 2 Protective film, improve the oxidation resistance and corrosion resistance of the coating; at the same time, silicon can also promote the interaction between the coating and the substrate; Cr in the liquid phase component 2 O 3 A protective film can be formed in the coating to block harmful substances such as oxygen and moisture from entering the interior of the coated substrate, thereby significantly slowing down the corrosion rate. Magnesium oxide can neutralize acidic substances such as sulfuric acid produced in combustion or chemical reactions, thereby reducing the corrosive effect of these acidic substances on metal materials. On the basis of the first corrosion-resistant coating, the second corrosion-resistant coating is prepared by laser cladding. In the process of preparing the second corrosion-resistant coating, the basic concept of high entropy alloy is introduced. Aluminum is used as the core element, which has good metallurgical bonding with the first corrosion-resistant coating. At the same time, due to the preparation method of laser cladding, the bonding with the first corrosion-resistant coating can be further strengthened at high temperature. The high-entropy high-temperature alloy as the outermost coating has low porosity and uniform composition. It has certain mechanical properties while being corrosion-resistant. The remaining Co, Ce, Ni and Ti can all improve the corrosion resistance of the coating, and the entire structure after adding the second corrosion-resistant coating has a high hardness and can extend the service life.

[0023] Furthermore, before laser cladding the second corrosion-resistant powder on the first corrosion-resistant coating, the surface of the high-temperature coating is cleaned with dilute hydrochloric acid, which can slightly etch the surface of the first corrosion-resistant coating, increase the roughness of the surface of the first corrosion-resistant coating, and enhance the bonding between the second corrosion-resistant powder and the first corrosion-resistant coating.

[0024] Furthermore, the second corrosion-resistant powder is dried before being clad on the first corrosion-resistant coating to avoid a certain amount of moisture in the second corrosion-resistant powder that affects the laser cladding process.

[0025] Furthermore, the second corrosion-resistant coating is prepared by a laser cladding method, and the bonding strength between the second corrosion-resistant coating and the first corrosion-resistant coating is significantly improved, thereby improving the overall performance of the coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a microscopic image of the corrosion-resistant composite coating of the present invention. DETAILED DESCRIPTION

[0027] The present invention is further described in detail below in conjunction with the accompanying drawings:

[0028] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0029] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0030] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0031] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0032] As mentioned in the background technology, with the development of industry, especially in high temperature environments, equipment such as boilers often face the problem of corrosion from high temperature gases. These high temperature gases may contain corrosive components such as hydrogen sulfide and carbon dioxide, which can cause serious corrosion to the metal parts of the boiler and affect the normal operation and safety of the equipment.

[0033] In order to solve the above problems, the first aspect of the present invention discloses a method for preparing a corrosion-resistant coating, comprising the following steps:

[0034] Step 1, pre-treating the substrate;

[0035] The substrate heat treatment comprises cleaning the substrate surface with anhydrous ethanol and deionized water alternately for several times; and preheating the substrate before performing step 2.

[0036] Among them, the preheating temperature is 220°C and the preheating time is 30-60min.

[0037] The substrate is targeted at common boiler tube wall materials, such as TP304H, TP347H, Super304H, TP347HFG, HR3C or nickel-iron based alloys.

[0038] Step 2: Preparation of the first corrosion-resistant coating

[0039] By mass fraction, 45-60% Al powder, 20-30% Si powder, 15-20% Al 2 O 3 powder and 1-5% NH 4 The mass ratio of Br powder is used to weigh Al powder, Si powder, Al 2 O 3 Powder and NH 4 Br powder is ball-milled to obtain the solid phase component. The ball-milling speed is 250rpm-400r / min and the ball-milling time is 6-24h.

[0040] In Al(H 2 PO4) 3 In the mixed solution of Cr 2 O 3and MgO as solutes, and the liquid phase components are obtained after mixing and stirring. 2 PO 4 ) 3 The mass fraction of 20-50%, the mass fraction of water glass is 15-25%, and the mass fraction of Cr 2 O 3 The mass fraction of Ni is 10-30%, and the mass fraction of MgO is 1-15%.

[0041] Mixing the solid phase component and the liquid phase component in a mixing ratio of 10 g: (3-7) mL, and then ball milling the mixture in a ball mill for 6-24 hours to obtain a first corrosion-resistant raw material, and coating the first corrosion-resistant raw material on the surface of the substrate, wherein the coating pressure during the coating process is 0.5-2.0 MPa, the coating thickness is 0.1-1.0 mm, and the raw material coverage rate coated on the substrate is not less than 98%;

[0042] After natural air drying for 24-48 hours, it is cured at 300-450℃ for 24-48 hours to improve the bonding between the first corrosion-resistant raw material and the substrate; then, it is heat treated at 980-1150℃ for 8-15 minutes under inert protective gas conditions to obtain the first corrosion-resistant coating. During the heat treatment process, the relationship between the various elements becomes closer, and the solvents therein can also evaporate at high temperatures.

[0043] Step 3, mix Al powder, Co powder, Cr powder, Ni powder, Fe powder and Ti powder, and mill them in a planetary ball mill at 200-300 r / min for 8-20 hours to obtain a second corrosion-resistant powder. When the second corrosion-resistant powder is mixed, the molar fraction of Al powder is 25%-30%, the molar fraction of Ti powder is 5%-10%, and the other four powders have equal molar fractions.

[0044] The second corrosion-resistant powder is laid on the first corrosion-resistant coating, and then laser cladding is performed. The laser cladding power is 2000-3000W, the scanning speed is 8-12mm / s, the powder feeding speed is 5-10g / min, the spot diameter is 3-5mm, the powder feeding gas and the protective gas are high-purity argon, and the cladding overlap rate is 40-50%.

[0045] As a preferred solution, the second corrosion-resistant powder after ball milling is dried in a drying oven at a drying temperature of 100-120° C. for 1-2 hours in a vacuum environment or a protective gas environment.

[0046] As a preferred solution, when preparing the second corrosion-resistant coating on the first corrosion-resistant coating, the residue on the first corrosion-resistant coating is washed away by a high-pressure water gun or a high-pressure air flow, and then naturally air-dried.

[0047] As a preferred solution, before placing the second corrosion-resistant powder on the first corrosion-resistant coating, the surface of the first corrosion-resistant coating is cleaned with dilute hydrochloric acid to etch the surface of the first corrosion-resistant coating, thereby increasing the roughness of the surface of the first corrosion-resistant coating and improving the metallurgical bonding performance between the second corrosion-resistant coating and the first corrosion-resistant coating.

[0048] The second aspect of the present invention discloses a corrosion-resistant composite coating prepared by the above-mentioned preparation method, comprising a first corrosion-resistant coating composited on a substrate, and a second corrosion-resistant coating composited on the first corrosion-resistant coating; the first corrosion-resistant coating is composed of Al, Si, Al 2 O 3 NH 4 Br, Cr 2 O 3 and MgO, and the second corrosion-resistant coating consists of Al, Co, Cr, Ni, Fe and Ti.

[0049] The following is further described in conjunction with specific embodiments.

[0050] Example 1

[0051] Step 1, pre-treating TP304H, washing it alternately with anhydrous ethanol and deionized water for 3 times, and preheating it at 220°C for 30 minutes.

[0052] Step 2: by mass fraction, 50% Al powder, 25% Si powder, and 15% Al 2 O 3 powder and 5% NH 4 The mass ratio of Br powder is used to weigh Al powder, Si powder, Al 2 O 3 Powder and NH 4 Br powder was ball-milled to obtain the solid phase component. The ball-milling speed was 250 r / min and the ball-milling time was 20 h to obtain the solid phase component.

[0053] In Al(H 2 PO 4 ) 3 In the mixed solution of Cr 2 O 3 and MgO as solutes, and the liquid phase components are obtained after mixing and stirring. 2 PO 4 ) 3 The mass fraction of Cr is 45%, the mass fraction of water glass is 25%, 2 O 3 The mass fraction of is 20%, and the mass fraction of MgO is 10%.

[0054] The solid phase component and the liquid phase component were mixed in a mixing ratio of 10 g:5 mL, and then ball-milled in a ball mill for 20 hours to obtain a first corrosion-resistant raw material. The first corrosion-resistant raw material was coated on the surface of the substrate. During the coating process, the coating pressure was 2.0 MPa and the coating thickness was 1.0 mm.

[0055] After natural air drying for 40 hours, the coating was cured at 350°C for 40 hours to improve the bonding between the first corrosion-resistant raw material and the substrate; and then the coating was heat treated at 1000°C for 10 minutes under inert protective gas conditions to obtain the first corrosion-resistant coating.

[0056] Step 3, mix 30% Al powder, 5% Ti powder, 16.25% Co powder, 16.25% Cr powder, 16.25% Ni powder and 16.25% Fe powder, by mole fraction, and ball mill them in a planetary ball mill at 250 r / min for 10 h to obtain a second corrosion-resistant powder.

[0057] The ball-milled second corrosion-resistant powder was dried in a vacuum drying oven at 100° C. for 2 h.

[0058] The dried second corrosion-resistant powder is laid on the first corrosion-resistant coating, and then laser cladding is performed. The laser cladding power is 3000 W, the scanning speed is 10 mm / s, the powder feeding speed is 10 g / min, the spot diameter is 5 mm, the powder feeding gas and the protective gas are high-purity argon, the cladding overlap rate is 40%, and the second corrosion-resistant coating is obtained.

[0059] See also Figure 1 , is a double-layer corrosion-resistant coating prepared in this embodiment. It can be seen from the figure that the prepared coating has uniform composition. The prepared composite coating has a thickness of about 350 μm, wherein the first corrosion-resistant coating is about 150-200 μm, and the second corrosion-resistant coating is about 200 μm thick.

[0060] Example 2

[0061] Step 1, pre-treating TP304H, washing it alternately with anhydrous ethanol and deionized water for 3 times, and preheating it at 220°C for 30 minutes.

[0062] Step 2: by mass fraction, 50% Al powder, 25% Si powder, and 15% Al 2 O 3 powder and 5% NH 4 The mass ratio of Br powder is used to weigh Al powder, Si powder, Al 2 O 3 Powder and NH 4 Br powder was ball-milled to obtain the solid phase component. The ball-milling speed was 400 r / min and the ball-milling time was 6 h to obtain the solid phase component.

[0063] In Al(H 2 PO 4 ) 3 In the mixed solution of Cr 2 O 3 and MgO as solutes, and the liquid phase components are obtained after mixing and stirring. 2 PO 4 ) 3 The mass fraction of Cr is 50%, the mass fraction of water glass is 24%, 2 O 3 The mass fraction of Ni is 25%, and the mass fraction of MgO is 1%.

[0064] The solid phase component and the liquid phase component were mixed in a mixing ratio of 10 g:4 mL, and then ball-milled in a ball mill for 10 hours to obtain a first corrosion-resistant raw material. The first corrosion-resistant raw material was coated on the surface of the substrate. During the coating process, the coating pressure was 1.0 MPa and the coating thickness was 0.5 mm.

[0065] After natural air drying for 45 hours, the coating was cured at 400°C for 30 hours to improve the bonding between the first corrosion-resistant raw material and the substrate; and then heat treated at 980°C for 15 minutes under inert protective gas conditions to obtain the first corrosion-resistant coating.

[0066] Step 3: Mix 30% Al powder, 5% Ti powder, 16.25% Co powder, 16.25% Cr powder, 16.25% Ni powder and 16.25% Fe powder, by mole fraction, and mill them in a planetary ball mill at 200 r / min for 20 h to obtain a second corrosion-resistant powder.

[0067] The ball-milled second corrosion-resistant powder was dried in a vacuum drying oven at 110° C. for 1 h.

[0068] The dried second corrosion-resistant powder is laid on the first corrosion-resistant coating, and then laser cladding is performed. The laser cladding power is 2000W, the scanning speed is 8mm / s, the powder feeding speed is 8g / min, the spot diameter is 4mm, the powder feeding gas and the protective gas are high-purity argon, the cladding overlap rate is 45%, and the second corrosion-resistant coating is obtained.

[0069] Example 3

[0070] Step 1, pre-treating TP304H, washing it alternately with anhydrous ethanol and deionized water for 3 times, and preheating it at 220°C for 30 minutes.

[0071] Step 2: by mass fraction, 50% Al powder, 25% Si powder, and 15% Al 2 O 3powder and 5% NH 4 The mass ratio of Br powder is used to weigh Al powder, Si powder, Al 2 O 3 Powder and NH 4 Br powder was ball-milled to obtain the solid phase component. The ball-milling speed was 400 r / min and the ball-milling time was 24 h to obtain the solid phase component.

[0072] In Al(H 2 PO 4 ) 3 In the mixed solution of Cr 2 O 3 and MgO as solutes, and the liquid phase components are obtained after mixing and stirring. 2 PO 4 ) 3 The mass fraction of Cr is 50%, the mass fraction of water glass is 25%, 2 O 3 The mass fraction of Ni is 10%, and the mass fraction of MgO is 15%.

[0073] The solid phase component and the liquid phase component were mixed in a mixing ratio of 10 g:3 mL, and then ball-milled in a ball mill for 15 hours to obtain a first corrosion-resistant raw material. The first corrosion-resistant raw material was coated on the surface of the substrate. During the coating process, the coating pressure was 0.5 MPa and the coating thickness was 1.0 mm.

[0074] After natural air drying for 35 hours, the coating was cured at 300°C for 48 hours to improve the bonding between the first corrosion-resistant raw material and the substrate; and then heat treated at 1150°C for 8 minutes under inert protective gas conditions to obtain the first corrosion-resistant coating.

[0075] Step 3, mixing 30% Al powder, 5% Ti powder, 16.25% Co powder, 16.25% Cr powder, 16.25% Ni powder and 16.25% Fe powder, by mole fraction, and ball milling them in a planetary ball mill at 300 r / min for 8 h to obtain a second corrosion-resistant powder.

[0076] The ball-milled second corrosion-resistant powder was dried in a vacuum drying oven at 120° C. for 2 h.

[0077] The dried second corrosion-resistant powder is laid on the first corrosion-resistant coating, and then laser cladding is performed. The laser cladding power is 2500W, the scanning speed is 12mm / s, the powder feeding speed is 7g / min, the spot diameter is 3mm, the powder feeding gas and the protective gas are high-purity argon, the cladding overlap rate is 50%, and the second corrosion-resistant coating is obtained.

[0078] Example 4

[0079] Step 1, pre-treating TP304H, washing it alternately with anhydrous ethanol and deionized water for 3 times, and preheating it at 220°C for 30 minutes.

[0080] Step 2: by mass fraction, 50% Al powder, 25% Si powder, and 15% Al 2 O 3 powder and 5% NH 4 The mass ratio of Br powder is used to weigh Al powder, Si powder, Al 2 O 3 Powder and NH 4 Br powder was ball-milled to obtain the solid phase component. The ball-milling speed was 300 r / min and the ball-milling time was 24 h to obtain the solid phase component.

[0081] In Al(H 2 PO 4 ) 3 In the mixed solution of Cr 2 O 3 and MgO as solutes, and the liquid phase components are obtained after mixing and stirring. 2 PO 4 ) 3 The mass fraction of Cr is 40%, the mass fraction of water glass is 20%, 2 O 3 The mass fraction of is 30%, and the mass fraction of MgO is 10%.

[0082] The solid phase component and the liquid phase component were mixed in a mixing ratio of 10 g:6 mL, and then ball-milled in a ball mill for 6 hours to obtain a first corrosion-resistant raw material. The first corrosion-resistant raw material was coated on the surface of the substrate. During the coating process, the coating pressure was 1.5 MPa and the coating thickness was 0.5 mm.

[0083] After natural air drying for 24 hours, the coating was cured at 450°C for 24 hours to improve the bonding between the first corrosion-resistant raw material and the substrate; and then heat treated at 1100°C for 12 minutes under inert protective gas conditions to obtain the first corrosion-resistant coating.

[0084] Step 3, mix 30% Al powder, 5% Ti powder, 16.25% Co powder, 16.25% Cr powder, 16.25% Ni powder and 16.25% Fe powder, by mole fraction, and ball mill them in a planetary ball mill at 250 r / min for 15 h to obtain a second corrosion-resistant powder.

[0085] The ball-milled second corrosion-resistant powder was dried in a vacuum drying oven at 120° C. for 1 h.

[0086] The dried second corrosion-resistant powder is laid on the first corrosion-resistant coating, and then laser cladding is performed. The laser cladding power is 2000 W, the scanning speed is 12 mm / s, the powder feeding speed is 6 g / min, the spot diameter is 4 mm, the powder feeding gas and the protective gas are high-purity argon, the cladding overlap rate is 45%, and the second corrosion-resistant coating is obtained.

[0087] Example 5

[0088] Step 1, pre-treating TP304H, washing it alternately with anhydrous ethanol and deionized water for 3 times, and preheating it at 220°C for 30 minutes.

[0089] Step 2: by mass fraction, 50% Al powder, 25% Si powder, and 15% Al 2 O 3 powder and 5% NH 4 The mass ratio of Br powder is used to weigh Al powder, Si powder, Al 2 O 3 Powder and NH 4 Br powder was ball-milled to obtain the solid phase component. The ball-milling speed was 400 r / min and the ball-milling time was 24 h to obtain the solid phase component.

[0090] In Al(H 2 PO 4 ) 3 In the mixed solution of Cr 2 O 3 and MgO as solutes, and the liquid phase components are obtained after mixing and stirring. 2 PO 4 ) 3 The mass fraction of Cr is 50%, the mass fraction of water glass is 22%, 2 O 3 The mass fraction of Ni is 20%, and the mass fraction of MgO is 8%.

[0091] The solid phase component and the liquid phase component were mixed in a mixing ratio of 10 g:7 mL, and then ball-milled in a ball mill for 24 hours to obtain a first corrosion-resistant raw material. The first corrosion-resistant raw material was coated on the surface of the substrate. During the coating process, the coating pressure was 1.0 MPa and the coating thickness was 0.5 mm.

[0092] After natural air drying for 48 hours, the coating was cured at 400°C for 35 hours to improve the bonding between the first corrosion-resistant raw material and the substrate; and then heat treated at 1000°C for 10 minutes under inert protective gas conditions to obtain the first corrosion-resistant coating.

[0093] Step 3, mix 30% Al powder, 5% Ti powder, 16.25% Co powder, 16.25% Cr powder, 16.25% Ni powder and 16.25% Fe powder, by mole fraction, and ball mill them in a planetary ball mill at 250 r / min for 10 h to obtain a second corrosion-resistant powder.

[0094] The ball-milled second corrosion-resistant powder was dried in a vacuum drying oven at 110° C. for 2 h.

[0095] The dried second corrosion-resistant powder is laid on the first corrosion-resistant coating, and then laser cladding is performed. The laser cladding power is 3000W, the scanning speed is 8mm / s, the powder feeding speed is 5g / min, the spot diameter is 4mm, the powder feeding gas and the protective gas are high-purity argon, the cladding overlap rate is 45%, and the second corrosion-resistant coating is obtained.

[0096] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a corrosion-resistant composite coating, characterized in that: The following steps are involved: Step 1, weighing Al powder, Si powder, Al2O3 powder and NH4Br powder according to the set mass, and obtaining a solid phase component after ball milling; using Al(H2PO4)3 and water glass as solvents, and using Cr2O3 and MgO as solutes, and mixing and stirring to obtain a liquid phase component; mixing the solid phase component and the liquid phase component to obtain a first corrosion-resistant raw material, coating the first corrosion-resistant raw material on the surface of the substrate, and obtaining a first corrosion-resistant coating after drying, curing and heat treatment; Step 2, mix Al powder, Co powder, Cr powder, Ni powder, Fe powder and Ti powder, obtain a second corrosion-resistant powder after ball milling, lay the second corrosion-resistant powder on the first corrosion-resistant coating, and obtain a second corrosion-resistant coating through laser cladding treatment; the molar fraction of Al powder in the second corrosion-resistant powder is 25% to 30%, the molar fraction of Ti powder is 5% to 10%, and the molar fractions of the other four powders are equal.

2. The method for preparing a corrosion-resistant composite coating according to claim 1, characterized in that: In step 1, the solid phase components are composed of 45-60% Al powder, 20-40% Si powder, 15-20% Al2O3 powder and 1-5% NH4Br powder by mass fraction.

3. The method for preparing a corrosion-resistant composite coating according to claim 1, characterized in that: In step 1, in the liquid phase components, the mass fraction of Cr2O3 is 10-30%, and the mass fraction of MgO is 1-15%.

4. The method for preparing a corrosion-resistant composite coating according to claim 1, characterized in that: In step 1, the mixing ratio of the solid phase component and the liquid phase component is 10g:(3-7)mL.

5. The method for preparing a corrosion-resistant composite coating according to claim 1, characterized in that: In step 1, the solid phase component and the liquid phase component are mixed by ball milling, and the ball milling time is 6-24 hours; the curing temperature is 300-450° C., and the curing time is 24-48 hours; the heat treatment temperature is 980-1150° C., and the heat treatment time is 8-15 minutes.

6. The method for preparing a corrosion-resistant composite coating according to claim 1, characterized in that: In step 2, before laying the second corrosion-resistant powder on the first corrosion-resistant coating, the surface of the first corrosion-resistant coating is cleaned with dilute hydrochloric acid.

7. The method for preparing a corrosion-resistant composite coating according to claim 1, characterized in that: In step 3, the ball milling speed during the ball milling of Al powder, Co powder, Cr powder, Ni powder, Fe powder and Ti powder is 200-300 r / min, and the ball milling time is 8-20 h.

8. The method for preparing a corrosion-resistant composite coating according to claim 1, characterized in that: The second corrosion-resistant powder is ball-milled and mixed and then dried at a temperature of 100-120° C. for 1-2 hours.

9. The method for preparing a corrosion-resistant composite coating according to claim 1, characterized in that: The laser cladding power is 2000-3000W, the scanning speed is 8-12mm / s, the powder feeding speed is 5-10g / min, the spot diameter is 3-5mm, the powder feeding gas and the protective gas are high-purity argon, and the cladding overlap rate is 40-50%.

10. A corrosion-resistant composite coating prepared by the method according to any one of claims 1 to 9, characterized in that: It includes a first corrosion-resistant coating compounded on a substrate, and a second corrosion-resistant coating compounded on the first corrosion-resistant coating; The first corrosion-resistant coating consists of Al, Si, Al2O3, NH4Br, Cr2O3 and MgO, and the second corrosion-resistant coating consists of Al, Co, Cr, Ni, Fe and Ti.